歯ブラシが側咽頭隙へ達した幼児の口腔内穿通性損傷の1例 - 藤田, 祐生; 清水, 英孝; 竹内, 憲民; 今井, 智章; 濱田, 正和; 道澤, 雅裕 (日本口腔外科学会雑誌, 2009)
Children often play with foreign objects such as a toothbrush in their mouths and sustain intraoral lacerations. Rarely, the objects penetrate into the parapharyngeal space and have to be surgically removed in cooperation with other specialties. We report a case of an intraoral penetration injury caused by a toothbrush entering the parapharyngeal space. A 2-year-old girl who was brushing her teeth before bedtime was intraorally impaled with a toothbrush after falling from an indoor jungle gym for infants. The patient was transferred to the emergency room in our hospital. CT scanning showed the toothbrush head near the internal carotid artery in the parapharyngeal space. Antibiotics were intravenously administered, and the foreign body was removed under general anesthesia, followed by wound suturing. The patient was discharged on the 7 day without any complications such as post-traumatic thrombosis of the internal carotid artery or deep neck abscess. It is important to adequately educate parents and their children about the dangers of a toothbrush as a foreign body that can cause serious penetration injuries.